Commentary: Embracing social sciences to improve population health. Issue 35 (14th August 2019) - Butler, Robb; Habersaat, Katrine Bach
Highlights: Reaching health goals relies on engaging, listening to and understanding communities. Social interventions and bio-social investigation are critical tools. This is recognized in academia but, in practice very rarely a routine measure. Authors call for guidance and tools to ensure implementation in practice.